Oszacowanie Odpowiedzi Struktury Mechanicznej na Dowolne Wymuszenie - C. Cempel (Engineering Transactions, 1973)
A method is proposed for estimation of the response of a mechanical system to an arbitrary excitation. Starting with a general model of the structure and three kinds of damping, the concept of maximum receptance playing the role of dynamic characteristics is presented. This concept is then used to determine the response of the structure to arbitrary types of harmonic excitations. When the excitation is considered as a random process, the corresponding variance of the response is derived. Numerical and experimental examples are given.